PENGARUH EKUITAS MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN CAT DULUX (Studi Kasus PT AKZONOBEL INDONESIA) - Agustinus Yanuar Heriyanto; Berlin Silaban (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
The purpose of this paper is to determine the effect of brand equity and prices on consumer paint purchasing decisions Dulux. The study was conducted by distributing questionnaires, while the research method was using Simple Random Sampling. T test shows that the calculated t value for brand equity (X1) is 2,843 and the calculated t value for the price (X2) is 2,373. all of which show greater than t table is 0,984. so the hypothesis stating brand equity and price has a partially positive effect on purchasing decisions of paint consumers in PT Akzonobel Indonesia, F Test, obtained F count> F table or 25,984 > 2,70 or significance level (sig) 0,000 < 0,05 so that the hypothesis stating brand equity and price together influences the purchasing decisions of paint consumers in PT Akzonobel Indonesia and the coefficient of determination show that brand equity and price contributed 37,7% to the purchasing decision of consumers of paint dulux PT Akzonobel Indonesia.